2018
DOI: 10.1177/1469787418782817
|View full text |Cite
|
Sign up to set email alerts
|

The effects of social media usage on attention, motivation, and academic performance

Abstract: Accessing social media is common and although concerns have been raised regarding the impact of social media on academic success, research in this area is sparse and inconsistent. Survey responses were collected from 659 undergraduate and graduate students to determine the relationship between social media usage and overall academic performance, as well as explore if this relationship is moderated by attention (regulation of time/study environment) and motivation (effort regulation). Both predictors, social me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 29 publications
2
20
0
5
Order By: Relevance
“…Ryan and Deci (2017) also postulated that the most autonomous forms of motivation, including intrinsic motivation, would lead to adaptive behaviour, cognitive and affective outcomes. Research also suggests that within the undergraduate student population in general, when integrating active learning and student-centred strategies in the teaching approaches, there is a consistent positive relationship between intrinsic motivation (Trevino and DeFreitas, 2014), self-efficacy (Sun et al, 2018) and academic achievement (Barton et al, 2018; Jeno et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ryan and Deci (2017) also postulated that the most autonomous forms of motivation, including intrinsic motivation, would lead to adaptive behaviour, cognitive and affective outcomes. Research also suggests that within the undergraduate student population in general, when integrating active learning and student-centred strategies in the teaching approaches, there is a consistent positive relationship between intrinsic motivation (Trevino and DeFreitas, 2014), self-efficacy (Sun et al, 2018) and academic achievement (Barton et al, 2018; Jeno et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, even though concerns on negative effects of social media on academic success have been reported in the literature, yet there is not sufficient research on this subject. Moreover, there are contradictions between the results of the available research (Barton et al., 2018).…”
Section: Conceptual Frameworkmentioning
confidence: 98%
“…In the literature, different studies have been conducted with the purpose of examining the relation between usage of social media environments and academic success where contradictory findings have been reached (Abdulahi, Samadi, and Gharleghi, 2014; Alwagait, Shahzad, and Alim, 2015; Barton et al., 2018; Khairi and Ghani, 2019; Owusu‐Acheaw and Larson, 2015). While in some studies, a negative relation between the use of social media environments and academic success was indicated (Karpinski et al., 2013), in other studies, relation level was reported to be very weak.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Pues, la utilización de las TIC junto con una metodología activa de enseñanza-aprendizaje contribuyen a fomentar la formación universitaria (Castillo-Montes y Ramírez-Santana, 2020). Además de que existe una correlación positiva entre el rendimiento académico de los estudiantes y la frecuencia de uso de Facebook con fines educativos (Lambić, 2016), así como la atención y motivación de usar Facebook en la educación también ayuda en el rendimiento del alumno (Barton, Adams, Browne y Arrastia-Chisholm, 2018). Lo cual justifica también la investigación para comprobar si en México existe un efecto positivo del uso de Facebook en el rendimiento académico universitario, pese a los problemas de infraestructura que se tienen.…”
Section: Introductionunclassified